Mechanisms in a Digitalized World - Gabrielle Demange (Center for Economic Studies and ifo Institute (CESifo), 2018)
Due to computing and communication facilities, formal procedures, often referred to as `algorithms', are now extensively used in public, economic and social areas. These procedures, currently at the forefront of criticisms, share some features with mechanisms as defined by economists, following Hurwicz. My aim is to investigate these relationships and to discuss some of the economic risks generated by the power of algorithms.
Keywords: D44; D47; D71; D82; 330; mechanisms; algorithms; algorithmic pricing and trading; social choice rule; data; Admission post-bac